(untitled) (LEARNing Landscapes, 2017)
The concept of “digital hygiene” addresses the way digital technology can be integrated into our lives in safe, healthy, responsible, and respectful ways. Teaching kids about digital hygiene requires parents to be confident about their role as models and guides for the use of these devices, which is difficult when adults feel—often quite justifiably—that their children’s tech skills outpace their own. This commentary addresses the need for broadening the notion of digital hygiene with input from kids and teens, then educating and supporting parents (and educators) in its application.